Fault lines in the Constitution : the framers, their fights, and the flaws that affect us today - Levinson, Cynthia; Levinson, Sanford, 1941- (Peachtree Publishers, 2017)
Gridlock! Gerrymandering! The Electoral college! How did our government get so complicated? As it turns out, many of the issues we struggle with today have their roots in the creation of the United States Constitution. Husband-and-wife team Cynthis Levinson and Sanford Levinson take us back to the beginnings of this document and show how these fault lines were first introduced - and how their unintended consequences continue to affect us today. The Framers of the Constitution, they remind us, faced many of the same challenges and disputes that we do in the twenty-first century. Sometimes there was conflict, sometimes compromise - and the Framers met most of the challenges with great skill and foresight. Some issues, however, were just too complex or controversial to settle in such a brief time. Today we are still suffering from the consequences of disputes and decisions made in an overheated room in 1787, as a new form of government for our country was being created. -- from dust jacket.